Importance of accurately assessing biomechanics of the cornea. Issue 4 (July 2016) - Roberts, Cynthia J.
Abstract : Purpose of review: This article summarizes the state-of-the-art in clinical corneal biomechanics, including procedures in which biomechanics play a role, and the clinical consequences in terms of error in estimating intraocular pressure (IOP). Recent findings: Corneal biomechanical response to refractive surgery can be categorized into either stable alteration of surface shape and thus visual outcome, or unstable biomechanical decompensation. The stable response is characterized by central flattening and peripheral steepening that is potentiated in a stiffer cornea. Two clinical devices for assessing corneal biomechanics do not yet measure classic biomechanical properties, but rather provide assessment of corneal deformation response. Biomechanical parameters are a function of IOP, and both the cornea and sclera become stiffer as IOP increases. Any assessment of biomechanical parameters must include IOP, and one value of stiffness does not adequately characterize a cornea. Summary: Corneal biomechanics plays a role in the outcomes of any procedure in which lamellae are transected. Once the corneal structure has been altered in a manner that includes central thinning, IOP measurements with applanation tonometry are likely not valid, and other technologies should be used.